Kualitas SDM, Penempatan Kerja dan Pengawasan Kerja sebagai Pembentuk Produktivitas Kerja Karyawan pada PT. PLN (Persero) UP 3 Medan - ariza fanny; Hafizah Hafizah; Rizky Putra (Universitas Harapan Medan, 2021)
This study aims to determine whether the quality of human resources, work placement and work supervision together as forming the work productivity of employees at PT. PLN (Persero) UP 3 Binjai either partially or simultaneously. The population used in this study were employees who worked at PT. PLN (Persero) Up.3.Binjai as many as 125 people, and the sample is 125 respondents using a census sample. The analysis technique used is multiple linear regression analysis The results showed that the quality of human resources as a shaper of employee productivity at PT. PLN (Persero) UP 3 Binjai, work placement as a form of employee productivity at PT. PLN (Persero) UP 3 Binjai, supervision is not a form of employee productivity at PT. PLN (Persero) UP 3 Binjai, simultaneously the quality of human resources, work placement and supervision together as a form of employee productivity at PT. PLN (Persero) UP 3 Binjai. Suggestions in this study are in the future, leaders should implement a supervisory system that is carried out systematically and suddenly so that later it can be known to what extent employees can work productively or not. Thus, the leadership can take the attitudes and actions needed to make the necessary improvements.